The gender pay gap in the former Yugoslav Republic of Macedonia - Kazandziska, Milka; Risteska, Marija; Schmidt, Verena (Skopje, 2012)
"The paper highlights how the majority of women occupy jobs in lower wage brackets compared to men. It also sheds light on how gender pay inequality is particularly stark for female workers with lower levels of educational attainment. Furthermore, it describes the various national mechanisms that have been set up to address gender based discrimination in the labour market and points to a curious, yet quite common, phenomenon- despite the laws and the institutions established to uphold gender equality (and despite the presence of a gender pay gap), the number of cases brought before these institutions is insignificant. This points to the importance of initiatives such as awareness creation on equality principles, laws and code of conduct to ensure equal opportunity laws and principles are applied fully and become the norm by which the labour market behaviours of women and men, workers and employers are shaped. Finally, this study is timely, coming just as the country witnessed the passing of a law on minimum wage. Since women are among the low wage earners, implementation of an effective minimum wage should serve to increase female wages and narrow the gender pay gap. We hope that this study will stimulate discussion and the identification of appropriate policy instruments to move closer to the goal of equal pay for work of equal value."